ANALISIS MANFAAT REBOISASI UNTUK PENGURANGAN KERUSAKAN ALAM DI DAERAH PESISIR PANTAI - Muhammadd Wirayuda Hafiz; Nuni Asnita Barasa; Putri Elda Sari; Masleni Nasution; Sari Wulandari (Nirta Learning Centre, 2025)
Reforestation of coastal areas is a key strategy in efforts to mitigate environmental damage, such as coastal abrasion, loss of mangrove habitat, and marine pollution, which threaten the sustainability of the ecosystem and the lives of coastal communities in Pantai Cermin, North Sumatra. This article analyzes the ecological and social benefits of the mangrove reforestation program and assesses its implementation from 2018 to 2024. Through a qualitative approach and literature study, research shows that reforestation not only improves coastal stability and reduces the risk of natural disasters, but also improves water and air quality, as well as increases people's environmental awareness. Despite challenges such as lack of funds, land conversion, and lack of oversight, a variety of strategic solutions have been implemented, including cross-sector collaboration and active community engagement. As a result, the area of mangrove areas rehabilitated has shown a positive trend, with a significant decrease in abrasion and an increase in the sustainability of marine biota habitats. This program proves that reforestation is an effective step in increasing the resilience and sustainability of coastal areas.